One‐Step Inkjet Printed Perovskite in Air for Efficient Light Harvesting (Solar RRL 2∕2018). Issue 2 (8th February 2018) - Liang, Chao; Li, Pengwei; Gu, Hao; Zhang, Yiqiang; Li, Fengyu; Song, Yanlin; Shao, Guosheng; Mathews, Nripan; Xing, Guichuan
Abstract : In article number 1700217, Yiqiang Zhang, Guichuan Xing and co‐workers demonstrate high performance perovskite solar cells based on CH3NH3PbI3 with a power conversion efficiency of up to 17.04% (0.04 cm 2 ) and 13.27% (4 cm 2 ). This is achieved via scalable near unity material utilization ratio one‐step inkjet printing method with innovative vacuum‐assisted thermal‐annealing post‐treatment and optimized solvent composition. The most efficient inkjet‐printed perovskite solar cell is reported here.